2007
DOI: 10.1111/j.1439-0434.2007.01250.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Peach latent mosaic viroid in Commercial Orchards of Peach in the North of Tunisia

Abstract: The presence of Peach latent mosaic viroid (PLMVd) was monitored during 2 years in peach orchards located in the North of Tunisia. PLMVd population was surveyed using a specific RT-PCR test adapted to crude sap extract. During the first year (2004), 228 samples were randomly selected in 22 peach orchards (eight cultivars) and tested for the presence of PLMVd. Results showed that PLMVd is highly and equally present in four regions of the North of Tunisia. Analyses of some key factors in relation to PLMVd incide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…In Tunisia, M. persicae attacks arable crops including potato, sugar beet and tobacco, horticultural crops in the families Brassicaceae, Solanaceae and Cucurbitaceae, and top fruit (especially peach, apricot and citrus). The greatest damage occurs in peach orchards and open field plantings of potato and tomato . The history of insecticide use against M. persicae in Tunisia mirrors that in many other countries with the efficacy of organophosphates, carbamates and pyrethroids having been progressively eroded by resistance .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Tunisia, M. persicae attacks arable crops including potato, sugar beet and tobacco, horticultural crops in the families Brassicaceae, Solanaceae and Cucurbitaceae, and top fruit (especially peach, apricot and citrus). The greatest damage occurs in peach orchards and open field plantings of potato and tomato . The history of insecticide use against M. persicae in Tunisia mirrors that in many other countries with the efficacy of organophosphates, carbamates and pyrethroids having been progressively eroded by resistance .…”
Section: Introductionmentioning
confidence: 99%
“…The greatest damage occurs in peach orchards and open field plantings of potato and tomato. 4,18 The history of insecticide use against M. persicae in Tunisia mirrors that in many other countries with the efficacy of organophosphates, carbamates and pyrethroids having been progressively eroded by resistance. 19 In the last decade, control of M. persicae has become increasingly reliant on neonicotinoid insecticides, although the continuing effectiveness of this class has also been questioned.…”
Section: Introductionmentioning
confidence: 99%
“…Peach latent mosaic disease occurs worldwide. The incidence of PLMVd in germplasm of different geographical origins is generally high and ranges from 40-90% (Fekih Hassen et al, 2007). Numerous studies have shown that PLMVd is transmitted by grafting, budding, contaminated blades or pollen, but not by seed (Hadidi et al, 1997;Desvignes et al, 1999;Barba et al, 2007;Faggioli & Barba, 2008).…”
Section: Introductionmentioning
confidence: 99%